2018
DOI: 10.5902/1980509832053
|View full text |Cite
|
Sign up to set email alerts
|

ABSORÇÃO E TRANSLOCAÇÃO DE SILÍCIO EM MUDAS DE <i>Eucalyptus camaldulensis</i>

Abstract: A busca pela alta produtividade e qualidade das plantas de eucalipto que sejam mais resistentes ao ataque de insetos-praga vem sendo cada vez mais estudada. Dentro deste contexto, realizou-se o estudo da absorção e a translocação de silício em plantas de Eucalyptus camaldulensis. O experimento foi realizado com o clone 58, em viveiro comercial da empresa Votorantim Siderurgia /João Pinheiro-MG, onde foi avaliada a aplicação de silício via solo (silicato de cálcio) e via foliar (silicato de potássio), com três … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The correlation between height and root dry matter was negative (-0.03). Studies developed with eucalyptus species (Eucalyptus camaldulensis and Eucalyptus urograndis) the application of silicon promoted an increase in the development and translocation of the nutrient in the seedlings (QUEIROZ et al, 2018;NAVAS et al, 2016). The increase in Si can be a viable technique for the production of lettuce seedlings, increasing morphological development (Gonzaga et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between height and root dry matter was negative (-0.03). Studies developed with eucalyptus species (Eucalyptus camaldulensis and Eucalyptus urograndis) the application of silicon promoted an increase in the development and translocation of the nutrient in the seedlings (QUEIROZ et al, 2018;NAVAS et al, 2016). The increase in Si can be a viable technique for the production of lettuce seedlings, increasing morphological development (Gonzaga et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Research on the topic is mainly developed for the production of forest and vegetable species seedlings, whose increment generated is economically viable (BRAGA et al 2009;GONZAGA et al, 2020;NAVAS et al, 2016;QUEIROZ et al, 2018), justifying the development of studies with cauliflower. In this sense, assuming that increasing dosage of silicon added to the substrate to form seedlings may favor the initial development of vegetables, the research aimed to analyze the increase in different proportions of silicon oxide to the substrate and the effects on cauliflower seedlings.…”
Section: Introductionmentioning
confidence: 99%
“…According to Ma and Yamaji (2015) and Queiroz et al (2018), eucalyptus is a non-Si accumulating species; for this reason, we chose to use the commercial fertilizer Sifol Powder as a source of Si in the presente study. Sifol Powder is an extremely pure reactive source of nanossílica that is more effective when applied via the roots than by foliar spray (Suriyaprabha et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Duarte ), allowing the authors to classify the studied plants as intermediate in the accumulation of this nutrient. Queiroz et al [36] have concluded that Eucalyptus camaldulensis is capable of absorbing and translocating Si and that these processes are higher at 60 days after application of different sources of this nutrient. These same authors explain that foliar application is more efficient than soil application and, as in the present study, eucalyptus cannot be classified as a Si accumulator plant.…”
Section: Discussionmentioning
confidence: 99%